A structural–functional diagnostic of Mpumalanga’s agricultural education and training system - Tim Fry; Aldo Stroebel; Sarah Cardey (South African Journal of Science)
Increasing capabilities are required to develop solutions to wicked problems whilst the economic, environmental, and social contexts of farming have become more turbulent. There is a growing focus on developing systemic capabilities that enable the identification, development, and scaling of shared solutions. This requires a cohesive agricultural education and training (AET) system that identifies needs of entire food systems and delivers responsive pedagogies that combine learning sources. However, South Africa’s AET system remains in dire need of governance reform directed towards greater integration. This study investigates the performance of the AET system in the Mpumalanga Province, South Africa, utilising an agricultural innovation system (AIS) lens to identify where there are absent or poor-quality infrastructures and interactions, and cognitive, regulatory, and normative institutions that hinder AET-system performance. Evaluations of AET-supportive innovation structures were coupled with articulations of innovation functions that support transdisciplinary demand articulation, knowledge co-development, and networking. Results highlight an absence of communication and coordination mechanisms, hindering vertical and horizontal interactions between multi-actor groups. This absence contributes to a disenabling environment for AET-supportive networking, facilitation, and brokerage, leading to missed opportunities to facilitate between food system actors and AET providers to develop transdisciplinary research and pedagogies that harness diverse knowledge, resources, and networks to maximise impact. Whilst there are industry-led needs assessment structures, these operate in silos and lack public sector engagement that could enable organisations with complementary mandates, knowledge, and infrastructures to respond to common priorities.